1994
DOI: 10.2307/3431769
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Arsenite Tolerance and Thermotolerance by Arsenite Occur by Different Mechanisms

Abstract: Both V79 and As/R28A cells (an arsenite-resistant Chinese hamster V79 cell variant) show increased resistance to toxic concentrations of arsenite after pretreatment with a nontoxic concentration. The induced tolerance can be completely inhibited by actinomycin D or cycloheximide. Pretreatment with a nontoxic heat shock (45°C, 10 min) resulted in a clear increased thermotolerance in both cell lines but failed to induce arsenite tolerance in either cell line. Pretreatment with arsenite induced a thermotolerance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Further genomic sequencing and identification of chromosomal ars operons in other bacteria will shed light on the evolution of this highly conserved and important bacterial operon. Moreover, recent results have shown this type of arsenic resistance mechanism in mammals (Wang & Rossman, 1993;Wang et al, 1994Wang et al, , 1996, supporting the notion that the protective function of ars operons has been strongly conserved in the course of evolution.…”
Section: Discussionsupporting
confidence: 65%
“…Further genomic sequencing and identification of chromosomal ars operons in other bacteria will shed light on the evolution of this highly conserved and important bacterial operon. Moreover, recent results have shown this type of arsenic resistance mechanism in mammals (Wang & Rossman, 1993;Wang et al, 1994Wang et al, , 1996, supporting the notion that the protective function of ars operons has been strongly conserved in the course of evolution.…”
Section: Discussionsupporting
confidence: 65%
“…It has been suggested by these investigators that human cells are less resistant to the chronic toxicity of As i due to the lack of an inducible, ef¯ux-mediated tolerance to arsenite (Rossman et al 1997) which has been observed in hamster cells (Wang and Rossman 1993;Wang et al 1996). The inducible arsenite tolerance observed in hamster cells involves de novo mRNA and protein synthesis and appears to be distinct from the ª heat shockº response observed for As i and other stressors (Wang, Hou, and Rossman 1994). Differences in cellular arsenite tolerance could possibly explain the greater susceptibility of humans to the noncancer effects of chronic As i exposure and, perhaps, to the carcinogenic effects as well.…”
Section: Noncancer Effects Of Inorganic Arsenicmentioning
confidence: 98%